Evaluación de un yogurt semidescremado con adición de mortiño (Vaccinium floribundum) elaborado con dos tipos de fermentos lácteos danisco (Yo-mix 883 lyo 50 dcu) y chr-hansen (fd-dvs yo flex mild 1.0), en la Universidad Estatal de Bolívar - Miño Vaca, Rommel David (2022)
The experimental part of the degree work was developed in the General Laboratory of the Faculty of Agricultural Sciences, Natural Resources and Environment of the State University of Bolivar, where the main objective was "To evaluate a semi-skimmed yogurt with the addition of mortiño (Vaccinium floribundum) made with two types of lactic ferments DANISCO (YO-MIX 883 LYO 50 DCU) and CHR-HANSEN (FD-DVS YO FLEX MILD 1.0). The raw materials under study were characterized and the fruit was selected according to INEN 1750 "sampling of fruits and vegetables", likewise the milk was tested for mastitis analysis, alcohol test and by means of the equipment called LACTOSCAN it was determined that this raw material complies with INEN 9 "Raw milk requirements", the sugar analysis was compared with INEN 259 "White sugar requirements". A type II semi-skimmed yogurt was prepared with the addition of mortiño jelly according to the design established in this research, likewise the mortiño jelly was prepared in accordance with INEN 415 "Vegetable preservatives, fruit jellies". By means of the sensory evaluation, the 8 treatments were submitted, of which the best was considered the yogurt fermented with CHR-HANSEN (FD-DVS YO FLEX MILD 1.0) at 40 °C of incubation for 3 hours. A bromatological analysis was performed on the best treatment and it was compared with the INEN 2395 standard "fermented milks" and with 1.15% of fat it complies with the standard. Finally, a label and production cost was made, which will be sold at 1.82$ in 1 L containers.